Investigation of tidal grounding line migration using SAR line-of-sight offset time series - Ramanath Tarekere, Sindhu; Krieger, Lukas; Floricioiu, Dana; Wuite, Jan (2024)
The abundance of past and current satellite-based SAR, laser altimetry and radar altimetry acquisitions have enabled timely and spatially extensive mappings of grounding lines for several outlet glaciers and ice streams of the Antarctic Ice Sheet. However, in addition to their actual locations, the grounding lines derived from tidal or dynamic methods include an ephemeral displacement induced by the tidal flexure of ice shelves. Previous works have demonstrated that grounding lines migrate with distances ranging from a few hundred meters to several kilometres heterogeneously and out of phase with ocean tides [1], [2], [3], [4], [5], [6], implying that the tidal component does not diminish in an interannual time series. Changes in the grounding line position over extended periods (several years to decades) provide insights into the stability and dynamics of ice sheets [7], [8] and thereby also impact the assessment of their evolution and contribution to sea level rise. We aim to quantify grounding line migration and model ice shelf flexure at tidal timescales. We employ a times series from 2019−2021 of line-of-sight (LOS) offsets from 6-day repeat cycle Sentinel-1 acquisitions over Larsen C Ice Shelf (LCIS) and Thwaites Glacier. The datasets were generated using the differential range offset tracking method outlined in [9]. Following the methodology of [10], we computed the Pearson’s correlation between LOS offsets and contemporaneous differential tide levels derived from the CATS2008 tide model [11]. Preliminary results show a strong correlation for LCIS and no significant correlation for Thwaites. We attribute this to the large tidal range (2 − 4 m) typical in the Weddell Sea compared to lower tide levels (< 1 m) in the Amundsen Sea and surmise that the rapid acceleration of the glacier tongue likely dominates the tidal signal in LOS. We also analyzed the range offset time series of pixels along multiple ice flow lines of LCIS. Despite experiencing the same differential tide level, we observed different ...